Study Of Customer Satisfactions In Agriculture Insurance In Review Of Product Dimension, Image And Responses (Case Study PT Asuransi Jasindo Branch Solo) - Primantono, Dimas Anindito (STIE AUB Surakarta, 2018)
This study aims to find out the Study Of Customer Satisfactions In Agriculture Insurance In Review Of Product Dimension, Image And Responses (Case Study PT Asuransi Jasindo Branch Solo). The location of research that is in use is Office of PT. Insurance Services Indonesia Solo. The population in this study is farmers who follow the agricultural insurance amounting to 100 people. Sampling in this study using questionnaire. the analytical techniques in this study consist of instrument testing, classical assumption test, multiple linear analysis, t test, F test and R² test. The result of this research proves the result of regression that the product has positive and insignificant impact on customer satisfaction, the image has a significant positive effect on customer satisfaction, while the responsiveness has a significant effect on customer satisfaction, but the result of the research is negative toward customer satisfaction. The result of t test shows that the quality, image, and responsiveness have significant effect to the satisfaction of the insurance customer while the product is not significant but the direction is positive. F test shows that together product, image, and responsiveness variables significantly influence Insurance customers' satisfaction variable with significance value 0,000 <0,050. the result of R² test shows that product, image, and responsiveness are able to explain 36,1% to the variable of farmer's customer satisfaction, while the rest equal to 63,9% explained by other variable not examined.Keywords: product, image, responsiveness, customer satisfaction.